Process and impact evaluation of the Odi Youth Center - Mokabane, Matshingwana Ellen (University of Limpopo (Medunsa Campus), 2010)
The primary purpose of Youth Centers is to provide adolescent reproductive health services, which includes equipping the youth with life-skills and knowledge that has potential to prevent the spread of HIV infections. The Adolescent Reproductive Health program of the Y centers includes information on sexual health, teenage pregnancy (including CTOP) and STI’s. These Youth Centers are located in various locations in South Africa, Mabopane being one. Y centers operates from the premise that, because information alone is not enough to make young people change behavior, young people also need the attitudes, motivation and negotiating capacity to put what they know into practice. Life Skills, a program that focuses on enabling young individuals to deal effectively with the demands and challenges of everyday life, is a key aspect of the program in youth centers. The program deals with building skills such as self-esteem, problem solving, assertiveness, and negotiation skills that are useful to young people in their everyday lives. This study evaluated the implementation of the youth program at the Odi Youth Center, which is in Mabopane, as well as the impact of the center on the lives of young people who utilize these services. The positive findings of the study were that young people in the area value the services offered at the centre and are grateful to this facility, crediting it with having provided them with knowledge and skills that enable them to deal with sexual and other social matters. However, they stated that the impact would be greater if the centre could open for longer periods during the week and also on Saturdays. HIV and AIDS education, which is a significant component of Youth Center programs, is provided by professional nurses who are employed by the Department of Health (North West Province). The centre also offers HIV counseling and testing, access to contraceptives including provision of condoms, diagnosis and treatment of STI’s. Young people reported that their knowledge of HIV is good because of the lessons they get from the centre. The study found the following areas of concerns, a. that the program implementation and activities do not follow a specific structure and occur haphazardly b. record keeping is poor c. the clinic staff who have been mandated to run the program have not been trained on the loveLife principles and youth friendly clinics d. the hours of operation for the Y center limits participation by the youth
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Health services; Life-skills; HIV; STI